Emotional Labor and Burnout in Nursing Profession - Jintarat, Bankchart; Sithisarankul, Pornchai (Journal of Preventive Medicine Association of Thailand, 2021)
Nursing profession is a profession that requires to be performed in accordance with the professional standard and expectations of the society. In addition to the use of physical strength to perform duties during office hours and overtime, nurses also have to use emotional labor to interact with their visitors. There are two types of emotional labor or the control of feelings at work including surface acting and deep acting. Although both types of strategies provide the same results, the uses of emotional resources are varied. Surface acting consumes more emotional resources than deep acting according to the theory of ego depletion. Therefore, if emotional labor is at an optimal level, it will be beneficial to nurses, patients, and hospitals. On the contrary, if emotional labor is at a too high level, it can lead to burnout eventually.